Reader's Digest Complete DIY Manual - Pub. by Reader's Digest (London Reader's Digest, 2000)
This collection contains all you need to know about practically every DIY job you can tackle, from changing a plug to re-wiring a house, and from painting a wall, to building one.
Includes Colored Ilustrarions and Index
Keywords: Do-it-yourself work